The efficacy and reliability of sequential adjuvant anthracycline-based chemotherapy and weekly paclitaxel regimen in human epidermal growth factor receptor 2 negative breast cancer: A retrospective analysis of a multicentre study - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2019)
Purpose: To analyze the reliability and the effectiveness of chemotherapy and prognostic factors for survival in patients with HER2 (human epidermal growth receptor 2) negative early-stage breast cancer treated with adjuvant sequential anthracycline-based chemotherapy and paclitaxel. Methods: This analysis retrospectively evaluated the medical records of 756 HER2 negative early-stage breast cancel-patients who received adjuvant sequential anthracycline-based chemotherapy and weekly paclitaxel in 15 medical oncology centers in Turkey between 2008-2015. Estrogen receptor (ER), progesterone receptor (PR), HER2, age, tumor size and grade, nodal status, perineural and lymphatic invasion, disease-free survival (DFS) and overall survival (OS) were analyzed. Results: The median patient age was 50 years (22-82). Median follow up period was 46 months (13-82). The rates of recurrence and death detected in this period were 14.8% and 7.4%, respectively.Median OS and PFS were not reached in this period. Five-year DFS and OS rates were 87% and 89%, respectively. Age (OR:0.35, 95%CI 0.12-0.96, p=0.04), PR status (OR:.0.44, 95%CI 0.18-1, p=0.05), lymphatic invasion (OR:.2.6, 95%CI 0.97-7.4, p=0.05) were independent prognostic factors.Most common grade 3-4 toxicides were fatigue (6.7%), neutropenia (1.7%) and nausea (1.3%). Neutropenic fever developed in 1.8% o f the patients and peripheral neuropathy in 16.9%. Dose reduction was necessary for 10%of the patients due to grade 3-4 toxicity, whereas postponement of chemotherapy was neccessary for 7% of the patients. Conclusions: This multicentric retrospective study confirmed that sequential adjuvant therapy with anthracycline-based chemotherapy and paclitaxel for HER2 negative breast cancer is an effective and reliable regimen.
Keywords: paclitaxel; anthracycline; adjuvant; breast cancer; DOXORUBICIN PLUS CYCLOPHOSPHAMIDE; PHASE-III; DOCETAXEL; OUTCOMES; THERAPY; TAXANES; TRIAL